1994
DOI: 10.1212/wnl.44.9.1710
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between visuospatial and representational neglect

Abstract: Using a quantitative measure, we analyzed the relationship between visuospatial and representational neglect in right- and left-brain-damaged patients and found signs of representational neglect only in right-brain-damaged patients. Although representational neglect was always associated with visuospatial neglect, suggesting that the two forms share a common underlying mechanism, the most frequent finding in right-brain--damaged patients was that of visuospatial neglect in isolation. A strong influence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
2
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(100 citation statements)
references
References 0 publications
7
87
2
1
Order By: Relevance
“…Bayesian inferential statistics (Crawford and Garthwaite, 2007) confirmed that these patients can be considered to suffer from neglect in number space. The incidence of 20% (4 out of 20) of patients suffering from neglect in physical and representational space lies in the spectrum reported by other investigators using non-numerical tasks, which range from 6% (Bourlon, Pradat-Diehl et al, 2008) to around 30% (Bartolomeo, Bachoud-Levi et al, 2005;Bartolomeo, D'Erme et al, 1994). While our data on the incidence of neglect in number space is in line with those of previous studies on the incidence of neglect for imagined space, it stands in contrast to the numerous articles reporting reliable rightward biases in mental number line bisection tasks (see Umiltà, Priftis et al, 2009).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Bayesian inferential statistics (Crawford and Garthwaite, 2007) confirmed that these patients can be considered to suffer from neglect in number space. The incidence of 20% (4 out of 20) of patients suffering from neglect in physical and representational space lies in the spectrum reported by other investigators using non-numerical tasks, which range from 6% (Bourlon, Pradat-Diehl et al, 2008) to around 30% (Bartolomeo, Bachoud-Levi et al, 2005;Bartolomeo, D'Erme et al, 1994). While our data on the incidence of neglect in number space is in line with those of previous studies on the incidence of neglect for imagined space, it stands in contrast to the numerous articles reporting reliable rightward biases in mental number line bisection tasks (see Umiltà, Priftis et al, 2009).…”
Section: Discussionmentioning
confidence: 65%
“…Thus, when neglect patients describe familiar places, maps or other geographical facts from memory, they may fail to name left-sided, but not right-sided landmarks of the imagined spatial layout (e.g., Bartolomeo, D'Erme et al, 1994;Meador, Loring et al, 1987;Rode, Rossetti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although different impairments may be at work in different neglect patients, some considerations seem to suggest that attentional impairments play a crucial role in most patients, thus justifying the naõ Ève impression that one may get from observing neglect patients' behavior. Considering, for example, the sensory modalities of expression of neglect, evidence indicates that, although neglect is by no means exclusive to visually presented material (which by itself challenges explanations based on a unimodal sensory de®cit [51]), when patients' performance in tactile or imagery tests is directly compared with their performance in visuospatial tests, neglect usually results more common and severe for visual than for nonvisual stimuli, as tactile [59±61] or imagined [62] events. Also for auditory neglect, it has been shown that blindfolding improves the ability of neglect patients to correctly localize sound stimuli originating on the left [63].…”
Section: Accounts Of Left Unilateral Neglectmentioning
confidence: 99%
“…Neglect was assessed using a battery of visuospatial tests (Bartolomeo, D'Erme and Gainotti, 1994), which included tasks of line cancellation, identification of overlapping figures and line bisection. A laterality score was assigned to each patient, indicating the magnitude of rightward bias.…”
Section: Subjectsmentioning
confidence: 99%
“…A laterality score was assigned to each patient, indicating the magnitude of rightward bias. A cut-off score was determined on the basis of the performance of a group of normal control subjects (Bartolomeo et al, 1994) (Figure 1). In the recovered group, patients R3 and R5 had received a training program specific for neglect, the remaining patients exhibited a spontaneous recovery.…”
Section: Subjectsmentioning
confidence: 99%